2021
DOI: 10.4314/ahs.v21i1.17
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hazardous drinking in university students from South Africa and Belgium: a cross-cultural comparison study

Abstract: Background: Previous studies have associated certain risk factors with hazardous drinking in students. However, big cultur- al and geographical differences exist regarding alcohol use. Objectives: To determine whether or not there was a difference in hazardous drinking between Belgian and South African university students and to establish the risk factors that contribute to hazardous drinking in university students (calculated using the AUDIT-C) from a developing country (South Africa) and a developed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…The present study showed that not being sports club members was associated with less likelihood to smoke and drink alcohol. These results are consistent with evidence where university students who joined sports groups or organisational sports are more likely to smoke and drink alcohol [ 51 54 ]. A systematic review by Lisha et al showed that university students in sports clubs reported higher levels of drinking and smoking than those who were not in any sports clubs [ 55 ].…”
Section: Discussionsupporting
confidence: 91%
“…The present study showed that not being sports club members was associated with less likelihood to smoke and drink alcohol. These results are consistent with evidence where university students who joined sports groups or organisational sports are more likely to smoke and drink alcohol [ 51 54 ]. A systematic review by Lisha et al showed that university students in sports clubs reported higher levels of drinking and smoking than those who were not in any sports clubs [ 55 ].…”
Section: Discussionsupporting
confidence: 91%
“…While the street-intercept method is useful within public health and development studies when traditional survey methods fall short or one is unable to obtain a representative sample, the sensitivity of the questionnaire and the environment in which data are collected can also impact the results [70]. In addition, previous research has linked hazardous drinking to a range of risk factors, including gender, age, socioeconomic factors such as parental income and level of education, and lifestyle [71]. The dynamics around exploring employment status as a contributing factor to alcohol consumption represent a complex issue that requires further exploration in the South African context, particularly since unemployment rates are so high amongst young adults [72,73] and more so because risk behaviour is prevalent amongst unemployed youth [74].…”
Section: Discussionmentioning
confidence: 99%
“…Study‐related stress is a global problem, and students from different countries show different patterns of behaviours to cope with the stress (Inaç et al., 2021). India is a country with a large young population, where the problem of disturbed mental health among youth is a growing concern (Reddy et al., 2018).…”
Section: Introductionmentioning
confidence: 99%